2021
DOI: 10.1371/journal.pntd.0009429
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up study (2007–2018) on American Tegumentary Leishmaniasis in the municipality of Caratinga, Minas Gerais State, Brazil: Spatial analyses and sand fly collection

Abstract: Background The municipality of Caratinga is an important endemic area for American Tegumentary Leishmaniasis (ATL) and no epidemiological studies were performed during the past two decades. Here, we analyzed the epidemiological situation and the geographical distribution of ATL cases in the municipality of Caratinga from 2007 to 2018 using geographic information systems (GIS) Also, we evaluated the impact of several demographic parameters in ATL distribution and the sand flies incriminated in its transmission.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 74 publications
(92 reference statements)
1
10
0
3
Order By: Relevance
“… 6 Studies published in the 1970s 6–8 and in 2021 5 showed that Caratinga is an ATL transmission area with rural and recent urban cases of the disease by Leishmania braziliensis . In our previous study, 5 those cases were in the north and southwest regions of the city overlapping with ATL proven vectors. This finding is of epidemiological relevance because of the urbanization of ATL is less common than visceral leishmaniasis.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“… 6 Studies published in the 1970s 6–8 and in 2021 5 showed that Caratinga is an ATL transmission area with rural and recent urban cases of the disease by Leishmania braziliensis . In our previous study, 5 those cases were in the north and southwest regions of the city overlapping with ATL proven vectors. This finding is of epidemiological relevance because of the urbanization of ATL is less common than visceral leishmaniasis.…”
Section: Introductionmentioning
confidence: 74%
“…In this study, an additional spatial analysis (2019–2019) following a previously published historical series (2007–2018) 5 is provided. We also collected sandflies in the municipality in urban and rural areas affected by ATL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…longipalpis in the last few decades, has adapted to be an urban or peri‑urban species (Souza et al., 2002; Rangel & Lainson, 2009; Fernández et al., 2012 ; Pinheiro et al., 2013 ; Salomón et al., 2009b ; María Soledad Santini et al., 2013 ; Dorval et al., 2016 ), Ny. whitmani is a species of forest and rural areas (Souza et al., 2002; Rangel & Lainson, 2009; Fernández et al., 2012 ; Pinheiro et al., 2013 ; Salomón et al., 2009a ; Santini et al., 2013; Dorval et al., 2016 ), but also shows a trend to colonize periurban areas (Rangel & Lainson, 2009; Santini et al., 2013; Neves et al., 2021 ; Santini et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%